Konsep Pengembangan Sumber Daya Manusia Berbasis Kompetensi, Bakat dan Ketahanan Dalam Organisasi - Nur Syahiroh; Syira Alegra Putri Fatekhah; Jovan Dwi Prasetyo; Mu’allimin Mu’allimin (Jurnal Budi Pekerti Agama Islam, 2024)
We often find organizations that are not running according to their goals or are less effective because they do not have the resources relevant to their needs. Some of these organizations will not survive in the long term in the competitive business landscape. In this case, Human Resource Development (HR) is a fundamental parameter for the success and achievement of the organization's goals to continue to exist. Based on a literature review, the concept of developing an HR organization needs to pay attention to aspects of employee competence, talent and resilience. The competency aspect is the potential for long-term value and a potential source of the company's competitive advantage. The talent aspect is an important point for a company to occupy the position it needs, and with the toughness aspect, employees are able to face competition and overcome difficulties to become opportunities to achieve greater achievements. Therefore, the vision, mission and hopes of an organization can bring success.